Infected “Mycotic” Aneurysm of the Common Carotid Artery—A Differential Diagnosis to Tumor of the Neck - Eriksen, Patrick R. G.; Hvilsom, Gitte B.; Homøe, Preben (Frontiers in Surgery, 2018)
Introduction: Infected “mycotic” aneurysm (IA) of the extracranial carotid artery is a rare condition that can be fatal if mistaken for other pathology. An 83-year-old man presented with a mass on the neck, initially suspected malignant. Weeks later it grew rapidly and was found to be an IA, thus acute surgery was necessary. Through this case report we discuss diagnostic obstacles and future perspectives on incidence of IA of the vessels of the neck. Case Report: Diagnostic imaging and clinical assessment suspected an unknown primary tumor of the neck. Fine needle aspiration was inconclusive. The patient did not present with any signs of infection or neurological symptoms; the only symptoms were discomfort and pain. Approximately two weeks later, the mass had grown and the patient became dysphagic, febrile and confused. Computed tomography angiography revealed an IA of the right common carotid artery. The patient underwent acute surgical removal of the pseudoaneurysm. Furthermore, ligation of the internal and external carotid arteries, and resection of the internal jugular vein was performed due to necrosis and thrombosis. After the operation, the patient became dysphonic due to paralysis of the right recurrent nerve. The pathogen found was E.coli, supposedly from the bladder after surgical urological intervention due to polyposis. Conclusion: IA is a very rare entity and can have many etiologies. Since it can be fatal, it is necessary to keep IA in mind when diagnosing masses in relation to vessels of the neck. As shown in this case, patients can present with atypical symptoms and with an unclear pathological genesis, since E.coli-induced IA is immensely rare. Epidemiological and microbiological markers indicate that we may see more cases in the future.